Understanding Behavioural Intention to Adopt E-Invoicing in The Case of Malaysia Small and Medium Enterprises (SMEs): A UTAUT2 - Ilias , Azleen; Baidi , Nasrudin; K. Ghani , Erlane; Muhammad , Kamaruzzaman (International Journal of Accounting and Economics Studies, 2026)
This study examines the behavioral intention to adopt e-invoicing among small and medium-sized enterprises (SMEs) in Malaysia, utilizing the UTAUT2 framework. E-invoicing provides benefits that enable businesses to exchange invoices electronically, enhancing operational efficiency and compliance while reducing costs. This research aims to examine the factors influencing SMEs’ intention to adopt e-invoicing and identify the most significant factors. A quantitative survey was conducted among SME owners who were preparing for the early adoption of e-invoicing. The questionnaire measured seven factors, including performance expectancy, effort expectancy, social influence, facilitating conditions, trust, security, and perceived risk. The findings revealed that social influence is the strongest positive factor influencing adoption intention, which may involve the roles of peer, professional, and regulatory pressures. In contrast, security concerns and perceived risk negatively influence behavioural intention, highlighting the importance of addressing data protection and system reliability for e-invoices developed by the government. Performance expectancy, effort expectancy, facilitating conditions, and trust were not significant factors in the Malaysian context. The study contributes theoretically by extending UTAUT2 to incorporate security and risk factors in the e-invoicing context. It offers practical insights for policymakers and software developers to support SME digital adoption effectively.
Keywords: E-Invoice; Unified Theory of Acceptance and Use of Technology 2; SMEs; Malaysia; technology adoption